Dampak Digitalisasi Media Sosial terhadap Empat Keterampilan Berbahasa Arab - Aminaturrahma, Aminaturrahma; Sumanta, Sumanta; Umayah, Umayah; Sa’dudin, Ihsan; Nurkholidah, Nurkholidah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the impact of digitalization of social media on four Arabic skills. This study uses a qualitative approach by applying descriptive methods. The results and discussion of this study show that digitization can be accepted and entered into various groups in Indonesia through its use in several applications. The impact of digitalization has also made Indonesians interested in social media. From this, social media can also be used to improve foreign language skills, including Arabic by using the features available in several of these applications, including Instagram. There are various features such as follow, direct message, photo upload, video upload, and others that can be used to hone the four Arabic language skills, namely Maharah al-Istima', al-Kalam, al-Qira'ah, and al-Kitabah. But for al-Kitabah (writing) in the application it can only be done by typing via the keyboard, while writing by hand is done offline. There are also accounts of other users who can provide education about Arabic. Therefore, this study recommends communities of Arabic language lovers or learners to develop shared language skills remotely both in Indonesia and abroad.